2012
DOI: 10.1111/ocr.12000
|View full text |Cite
|
Sign up to set email alerts
|

Tooth eruption: altered gene expression in the dental follicle of patients with cleidocranial dysplasia

Abstract: The observed alterations in the expression and ratios of the aforementioned factors in the dental follicle of CCD individuals suggest a disturbed paracrine signaling for bone remodeling that could be responsible for the impaired tooth eruption seen in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
2
20
0
3
Order By: Relevance
“…These results indicate that DFCs RUNX2+/m can impair osteoclastogenesis in the local region during tooth eruption. Other studies had also reported that RUNX2 mutation could markedly restrict the ability of DFCs and PDLCs to induce osteoclasts differentiation, which was consistent with the results in the current study (Dorotheou et al., ; Ge et al., ; Lossdorfer et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that DFCs RUNX2+/m can impair osteoclastogenesis in the local region during tooth eruption. Other studies had also reported that RUNX2 mutation could markedly restrict the ability of DFCs and PDLCs to induce osteoclasts differentiation, which was consistent with the results in the current study (Dorotheou et al., ; Ge et al., ; Lossdorfer et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…More recent studies of dental follicle cells (DFC) from patients with CCD have reported disturbed osteoclast‐inductive signalling in DFCs, which the authors suggest could be responsible for delayed tooth eruption in patients with CCD . Sun et al .…”
Section: Cleidocranial Dysplasiamentioning
confidence: 99%
“…LOSS-D € ORFER et al (66) carried out an in vitro study on human periodontal ligament cells from two patients with CCD and found that these cells showed a reduced capacity to induce the differentiation of active osteoclasts. More recent studies of dental follicle cells (DFC) from patients with CCD have reported disturbed osteoclast-inductive signalling in DFCs, which the authors suggest could be responsible for delayed tooth eruption in patients with CCD (67)(68)(69). SUN et al (70) isolated and cultured DFCs and periodontal ligament cells (PDLCs) from an 11-yr-old individual with CCD and concluded that the RUNX2 mutation disturbs the modulatory effects of both DFCs and PDLCs on the differentiation of osteoclasts and osteoblasts, thereby interfering with bone remodelling.…”
Section: Animal Models and Molecular Studiesmentioning
confidence: 99%
“…Cleidocranial dysplasia (CCD), which is caused by mutation of Runx2, is a hereditary congenital disorder characterized by the abnormalities of bone development such as clavicle dysplasia, unclosed fontanels, and retained primary teeth due to no root resorption [11][12][13][14][15][16]. Previous studies reported that Runx2, which is the master osteogenic transgenic factor regulating osteogenesis metabolism, also induces differentiation of osteoclast through regulation of RANKL and OPG [17][18][19][20][21].…”
mentioning
confidence: 99%